Cadmium accumulation in soils developed from limestone and leaching characteristics of cadmium during development of the soils in western Zhejiang Province - ZHANG Shuang; ZHANG Mingkui (浙江大学学报. 农业与生命科学版)
In order to understand the geochemical characteristics of soil cadmium (Cd) during weathering and soil formation of limestone, three types of limestone soils were sampled at the same time from western Zhejiang Province. The Cd enrichment in limestone hills and nearby valleys and the vertical distribution of Cd in the soil profiles were studied. The leaching characteristics of Cd during development of the soils were analyzed by mass balance method with reference to stable element zirconium (Zr), and the results were also compared with those of yellowish red soils developed from local shale. The results showed that the leaching and accumulation of Cd in the limestone soils occurred simultaneously. Because of the special soil-forming process of limestone, the enrichment of Zr and Cd in the soils was obvious, and the enrichment amounts of soil Cd in limestone hills and nearby valleys were obviously higher than that of shale-derived hilly soil in the same area. The vertical distribution of Cd in three kinds of limestone soils had obvious differences and the chemical forms of Cd in different limestone soils were also different. The high leaching characteristics of Cd in the soils during weathering of limestone and the surface erosion of the limestone soils with high Cd content may be the main reasons for the high Cd accumulation in the soils in the limestone distribution area and its vicinity.